Misuse of Personal Data for Commercial Purposes on Facebook Social Media as a Digital Crime and Legal Certainty for Users - Sarah Mouw; Fricean Tutuarima; Ridwan Hatala (JETISH: Journal of Education Technology Information Social Sciences and Health, 2023)
This research is a qualitative descriptive study that aims to determine student perceptions related to personal data violations for commercial purposes on social media Facebook as a digital crime and legal certainty for users. This research was conducted in Ambon City, Maluku. Data collection was carried out through interviews with a number of informants who were considered to be directly involved, namely those who had been victims of personal data attacks on Facebook social media. The results of the study show that several forms of personal data attack have been experienced by Facebook users, namely, hacking with malicious intent (cracking), malicious software attacks (malware), identity theft (identity theft), and fraud by fraudsters (fraudsters), causes of data theft. These individuals exist purely because of the intent of the perpetrator or are also responsible and careless of the owner (subject) of the personal data. Laws and regulations discuss rights and obligations, prohibitions, sanctions and punishments, but cannot automatically protect personal data so that public education on the importance of protecting personal data will support the personal data it protects.